Upaya Tenaga Pendidik Dalam Meningkatkan Kualitas Pembelajaran Dengan Kurikulum Merdeka Belajar Di SMK St. Nahanson Parapat Sipoholon Tahun 2023 - Loria Simanungkalit; Betty Pakpahan; Lasmaria Lumban Tobing (Simpati, 2023)
The aim of this research is to describe the efforts of teaching staff in improving the quality of learning with the independent learning curriculum at St. Vocational School. Nahanson Parapat Sipoholon. The method used in this research is a descriptive qualitative research method with a phenomenological approach. Data collection was carried out using observation, interviews and documentation techniques. The results of this research describe the efforts of teaching staff in improving the quality of learning with an independent curriculum at St. Vocational School. Nahanson Parapat Sipoholon in 2023 by: delivering interesting learning, getting students used to asking questions, and attending seminars/training. This research concludes that the efforts made by teaching staff to improve the quality of learning with an independent learning curriculum are very necessary at St. Nahanson Parapat Sipoholon Vocational School so that the quality is higher and student achievement increases.